Taking stock: Is recovery of a depleted population possible in a changing climate?. (17th June 2022) - Langan, Joseph A.; Bell, Richard J.; Collie, Jeremy S.
Abstract: As the impacts of climate change become more severe throughout the global oceans, fisheries managers will be increasingly challenged to rebuild stocks exhibiting declining productivity. In such cases, detailed knowledge of species life history will be necessary to both restrict harvest and manage other environmental conditions, where possible, that impact survivorship. A current example of these challenges, the Southern New England/Mid‐Atlantic Bight winter flounder stock remains in a persistently depleted state due to a combination of past harvest and the effects of climate change mediated through increased predation. To explore the recovery capacity of a subpopulation of this stock, a life‐cycle model was fit to 29 year classes of stage‐specific winter flounder data from surveys conducted in Narragansett Bay, Rhode Island and used to project future subpopulation abundance. Supporting a prevailing hypothesis, the results indicated that environmental factors influencing juvenile mortality were largely responsible for inhibiting recovery. Furthermore, recovery of the subpopulation to past levels of abundance was determined to be unlikely even under optimistic future conditions resulting from aggressive management interventions. Taken together, the findings of this work pose important questions regarding the realism of assessing climate‐challenged populations against biological reference points set under past environmental regimes and the degree to which harvest restrictions to promote recovery of such stocks should be allowed to limit warm‐water fisheries thriving in a warming ocean.